(untitled) (Palimpsesto, 2017)
Enrolled in the intersection between intellectual history and the history of the book and the edition, the article analyzes the Argentine political radicalization of the seventies through the critique of the world of books and the edition formulated by two avant-garde films, La hora de los hornos and Alianza para el progreso, and two magazines of the new intellectual left, Cristianismo y Revolución and Los Libros. These diverse cultural objects not only critically represented the relationship of intellectuals to books and the linking of authors with the market, the public and reading, but also offered themselves as models for the renewal of aesthetic languages and instruments valid for Revolutionary transformation of society and culture.